Predicting deliberate self-harm in adolescents: a six month prospective study. - O'Connor, R; Rasmussen, S; Hawton, K (2009)
Few studies have investigated the extent to which psychosocial/psychological factors are associated with the prediction of deliberate self-harm (DSH) among adolescents. In this study, 737 pupils aged 15-16 years completed a lifestyle and coping survey at time one and 500 were followed up six months later. Six point two percent of the respondents (n = 31) reported an act of DSH between Time 1 and Time 2. In multivariate analyses, worries about sexual orientation, history of sexual abuse, family DSH, anxiety, and self-esteem were associated with repeat DSH during the course of the study, but history of sexual abuse was the only factor predictive of first-time DSH. The findings suggest that school-based programs focused on how young people cope with psychosocial stressors may offer promise.